The Effect of Foot Massage on Hemodynamic among Patients Admitted in to the Intensive Care Unit of General Public Hospital, Indonesia - Putri C, Nyayu Nina; Permana, Bhakti; Lindayani, Linlin (KnE Life Sciences, 2021)
Several studies have suggested the effectiveness of foot massage on reducing stress and blood pressure. However, few studies examine the effect of foot massage on hemodynamic status especially among patients admitted to intensive care units, when the hemodynamics status was unstable and became a significant concern. This study aimed to examine the effects of on hemodynamic status especially among patients admitted to intensive care unit. This study was quasi-experimental with pre- and post-test in one group. Subjects were recruited from the intensive care unit of one general public hospital located in Garut, West Java, Indonesia. Patients who used a partial mode control of ventilator, mean arterial pressure > 70 mmHg, heart rate > 60 times per minute, respiration rate > 12 times per minutes, and oxygen saturation ≤ 100% were considered as eligible criteria in this study. The exclusion criteria were patients who have fractures, trauma, or leg injuries, in an anxious state, or diagnosed with deep vein thrombosis symptoms. A paired t-test was used to examine the effect of the intervention of mean arterial pressure, heart rate, respiration rate, and oxygen saturation. Of the 30 patients recruited, the mean age was 41.7 (SD=3.10) with the majority female (63.3%). We found that foot massage has a significant impact on the improvement of the mean arterial pressure, heart rate, respiration rate, and oxygen saturation at the second time measurement after 30 minutes intervention (p<0.05). Foot massage improves the hemodynamic status among patients admitted in intensive care unit. Future studies using a rigor method with large sample size is needed with control therapy and disease-associated factors. Keywords: foot massage, hemodynamic, intensive care unit, intervention study